The Efficacy of Combination Therapies Including Antiviral Drugs, Methylprednisolone and Daily Proning in 20 Patients with COVID-19 Requiring Invasive Mechanical Ventilation-Case Series in A Single Critical Care Center in Osaka, Japan - Shimazu, Haruka; Yoshiya, Kazuhisa; Maruyama, Shuhei; Kanayama, Shuji; Matsunami, Shuhei; Iwamura, Hiromu; Wada, Daiki; Yoshihara, Tomoyuki; Saito, Fukuki; Nakamori, Yasushi; Kuwagata, Yasuyuki; </g, (Archives of Clinical and Medical Case Reports, 2020)
Background: Since December 2019, the COVID-19 infection has drastically spread across China and the world, including Japan. Few reports so far have clarified the prognosis and treatment of critically ill patients managed with invasive mechanical ventilation. We describe the clinical courses and detail treatments of 20 critically ill patients with invasive mechanical ventilation, which may be valuable for determining future therapies and intensive care of critically ill patients with COVID-19. Methods: We carried out descriptive analysis for 20 critically ill patients with laboratory-confirmed SARS-CoV-2 infection who were admitted to our hospital ICU and required invasive mechanical ventilation. The patients’ general characteristics, laboratory data, treatments, and outcomes were assessed between survivors and non-survivors. Results: Among 20 patients, 14 patients survived and 6 patients died. The lowest lymphocyte cunt (93 vs 279/μL, p<0.01) and platelet count (12 vs 152 × 103/μL, p<0.01) were significantly lower, and the highest KL-6 value (1584 vs 546 U/mL, p=0.02) was significantly higher, in non-survivors during ICU stay. In addition to antiviral treatments and daily proning of the patients, methylprednisolone was administered to all patients to control cytokine storm syndrome following the virus infection. Six patients died from complications, but no patients died of respiratory failure. As a result, none of the patients required ECMO. Conclusion: We conducted multidisciplinary treatments using a single protocol, including antiviral drugs, methylprednisolone and daily proning, for critically ill COVID-19 patients who required invasive mechanical ventilation. Out protocol was effective in our ICU and may be valuable for determining future therapies of COVID-19. <gdiv></gdiv>